The truce : progressives, centrists, and the future of the Democratic Party - Walker, Hunter; Luppen, Luppe B. (W.W. Norton & Company, 2024)
"Even before the cataclysmic 2016 election, the Democratic Party had long been at war with itself-yet Joe Biden's narrow victory in 2020 bridged the divide. Facing the dire threat of a second Trump administration, Democrats forged an unlikely but effective coalition that stalled Trumpism at the ballot box and enacted a raft of consequential legislation. But how long can the uneasy peace hold, and can Biden win again?"--